Determination of fungicides in sediments using a dispersive liquid–liquid microextraction procedure based on solidification of floating organic drop. Issue 11 (13th April 2014) - Dong, Sheying; Huang, Guiqi; Lu, Jinsuo; Huang, Tinglin
<x xml:space="preserve">Abstract</x> A dispersive liquid–liquid microextraction procedure based on solidification of floating organic droplet has been investigated for the determination of fungicides (cyprodinil, difenoconazole, myclobutanil, and spiroxamine) in sediments by HPLC with diode array detection. In the overall extraction process, the extraction solvents can be separated easily from the sample solution, and the experiment time was shortened. Moreover, several parameters such as the type and volume of the extraction solvent and dispersive solvent, centrifugal speed, extraction time, and salt effect that affect the extraction efficiencies of the target fungicides were studied and optimized. Under the optimized conditions, the LOD for the target analytes were in the range of 0.1–0.5 μg/g. Satisfactory recoveries of the target analytes in the sediment samples were 81.00–99.00%, with RSDs (n = 5) that ranged from 1.8 to 6.5%. Finally, the simple, sensitive, and environmentally friendly method was successfully applied to determine the target fungicides in actual sediment samples.